Examination of the Effect of Transaction Costs in the Hungarian Beef Sector - Bárdos, Krisztina (Acta Agraria Debreceniensis, 2004)
technical and economic characteristics, which give rise to high levels of uncertainty and greater control in the supply chain. In order to investigate the role of different transaction costs in marketing behavior, we carried out research in the central region of Hungary among beef retailers and wholesalers. This research is based on primary data collection and examines the motivation of choices in the beef sector on distinction among different marketing channels and the role of transaction costs in procurement. Since this case can be regarded as a qualitative choice situation the hypothesis that transaction cost’s variables are significant is judged by the application of multinomial logit model in order come up with the variables that can influence the supply chain structure and the choice of different marketing channels. This analysis enabled us to explore the structure in data and confirm or reject the expected interrelations of causative variables. Our 1 A szerző témavezetője Dr. Fertő Imre. 2 A kutatás az OTKA F038082 sz. „Vertikális koordinációs és integrációs modellek az élelmiszer-gazdaságban” c. programja keretében valósult meg. 3 A szerző köszöni Dr. Fertő Imrének és Dr. Szabó G. Gábornak, a Magyar Tudományos Akadémia Közgazdaságtudományi Kutatóközpont tudományos főmunkatársainak a kutatás során nyújtott nagy értékű segítséget. results partly support and contradict the basic predictions of transaction cost economics.